Using black PMMA to investigate losses in fibre laser cutting - Atiyah, Hasanain Kareem (2019)
Fibre laser cutting technology has become interestingly prevalent. There is an associated interest in ensuring the process is efficient. This can be done by investigating how much laser light passes through the cut without being absorbed. Beam prints can be useful in terms of quantifying how much light is lost from the process, as well as indicating the nature of the reflections taking place in the cut zone. Beam prints in poly-methyl methacrylate (PMMA) has previously been shown to be useful as a cheap analytical tool for CO2 cutting. However, transparent PMMA cannot be used in fibre laser cutting as it does not absorb the fibre laser wavelength of 1.06µm. Previous work with fibre lasers has established that certain black grades of acrylic are highly absorptive of 1 micron wavelength [1, 2]. Previous attempts to use black PMMA in quantitative work have reported that the energy required to evaporate a one unit volume depended on scanning speed [1, 3]. This would require an, inconvenient, calibration exercise to be carried out for any specific experimental set up. This thesis investigates how Carbon Filled Black Acrylic (CFBA) can be used to quantify losses in fibre laser cutting. A series of experiments are carried out and determine a specific evaporation energy of 3.4J/mm3 for black PMMA. However, this figure is only applicable when two key conditions are met: 1. The laser beam is intense enough not to be affected by the threshold effect and 2. There is effective flushing of the plume of vapour which contains the monomer and carbon dust cloud which can otherwise absorb the laser irradiation. When these two conditions are met, CFBA can be used as a cheap analytical tool for fibre laser cutting. Quantitative results reported in this thesis confirm that the energy lost from the cut front decreases with increases cutting speed. This means that the efficiency of the cutting process increases with increasing cutting speed. A novel laser cutting set up is developed where the CFBA remains stationary with respect to the cutting head. This produces distinct “leaf” prints which can provide quantitative and qualitative information about the transmission and reflection of light in the cutting zone. Comparison with some basic modelling work confirm that key dimensions of the leaf prints can be linked to the cut front inclination and kerf walls. Further modelling work is required to fully understand all the information contained in.